KEMAMPUAN BERPIKIR KOMPUTASI MATEMATIS MAHASISWA DALAM MEMAHAMI MATERI EKSPONENSIAL PADA MATA KULIAH MATEMATIKA DASAR - Khomeni, Ayathollah; Rhamayanti, Yuni (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2025)
This study aims to analyze the mathematical computational thinking abilities of students in understanding exponential material in the Basic Mathematics course. The research was conducted on first-semester students of the Vocational Education and Informatics Program at the Tapanuli Selatan Institute of Education, with a sample size of 40 students. The method used was descriptive research with a qualitative data analysis technique based on the model of Miles and Huberman (2003), through the stages of data reduction, data presentation, and conclusion drawing. Students' mathematical computational thinking abilities were analyzed based on the indicators of problem decomposition, pattern recognition, abstraction, and algorithmic thinking. The results showed that the students' mathematical computational thinking abilities in solving exponential problems were mostly in the moderate category (50%), with 22.5% of students having high or very high abilities. However, 22.5% of students still showed low to very low abilities in solving problems. This study concludes that although most students are able to identify and solve mathematical problems computationally, there is still a need for improvement in computational thinking abilities, especially in pattern recognition and abstraction. This study contributes to the development of mathematics education, particularly in preparing students to face the challenges of the digital era, which demands computational thinking skills.